Respuesta :
Answers:
a) [tex]F_{g}=735 N[/tex] and [tex]n=732.47 N[/tex], hence [tex]F_{g} > n[/tex]
b) [tex]n_{poles}=735 N[/tex] [tex]n_{equator}=732.47 N[/tex]
Explanation:
a) At the equator, both the centripetal force [tex]F_{c}[/tex] and the gravitational force [tex]F_{g}[/tex] (also called true weight) are directed "downward", while the normal force [tex]n_{equator}[/tex] (also called apparent weight) is directed "upward". Therefore we have the following equation:
[tex]n_{equator}-F_{g}=-F_{c}[/tex] (1)
Where:
[tex]F_{g}=m g[/tex] being [tex]m=75 kg[/tex] the mass and [tex]g=9.8 m/s^{2}[/tex] the acceleration due gravity
[tex]F_{c}=m a_{c}[/tex] being [tex]a_{c}=0.0337 m/s^{2}[/tex] the centripetal acceleration at the equator
According to this (1) is rewritten as:
[tex]n_{equator}-mg=-m a_{c}[/tex] (2)
Isolating [tex]n_{equator}[/tex]:
[tex]n_{equator}=-m a_{c} + mg[/tex] (3)
[tex]n_{equator}=m(-a_{c}+g)[/tex] (4)
[tex]n_{equator}=75 kg (-0.0337 m/s^{2}+9.8 m/s^{2})[/tex] (5)
[tex]n_{equator}=732.47 N[/tex] (6) This is the apparent weight at the equator
The true weight is given by [tex]F_{g}=m g=75 kg (9.8 m/s^{2})[/tex]
Hence: [tex]F_{g}=735 N[/tex] (7)
As we can see [tex]F_{g} > n_{equator}[/tex]
b) Now we have to calculate the apparent weight at the poles [tex]n_{poles}[/tex]:
[tex]n_{poles}-F_{g}=-F_{c-poles}[/tex] (8)
Since [tex]F_{c-poles}=0[/tex] (8) is rewritten as:
[tex]n_{poles}=F_{g}[/tex] (9)
[tex]n_{poles}=m g[/tex] (10)
[tex]n_{poles}=(75 kg)(9.8 m/s^{2})=735 N[/tex] (11)
So, the apparent weight of the person at the poles is 735 N and at the equator is 732.47 N